DNA analysis of Huntington's disease in southern Chinese. Issue 2 (February 1995) - Chan, V; Yu, Y L; Chan, T P; Yip, B; Chang, C M; Wong, M T; Chan, Y W; Chan, T K
Abstract : Allelic frequencies of RFLPs at loci closely linked to the HD gene, D4S95, D4S91, D4S141, and D4S90, were determined in 13 Huntington's disease (HD) patients from nine Chinese families and 129 normal subjects. These were similar for non-HD and HD chromosomes and the HD gene in Chinese is associated with multiple haplotypes. Hence the HD gene probably arose independently in the background haplotypes of the Chinese population. The heterozygosity rates for the two most useful RFLP sites are 0.659 for D4S95-AccI VNTR and 0.494 for D4S141-HindIII. (CAG)n repeat numbers ranged from 12 to 27 in 174 normal chromosomes. In 52 meiotic recombinations, the (CAG)n repeats were stably inherited in normal families. In HD families, 12 of 13 HD patients had expanded (CAG)n repeats of 40 to 58. Additionally, 10 asymptomatic family members had expanded (CAG)n repeats and the inheritance of the expanded repeat was unstable in these families.